Verifikasi Metode Penetapan Kadar Fenol Total Cara Folin-Ciocalteu - Dewi Primayanti Laela (Jurnal Pengelolaan Laboratorium, 2025)
The Biofarmaka Laboratory is currently preparing for ISO/IEC 17025 accreditation, which requires the use of validated analytical methods and verified procedures for standard methods. This study aims to support the verification of a method for determining total phenolic content using the Folin–Ciocalteu reagent, as outlined in the Indonesian Herbal Pharmacopoeia, First Edition (2013). Verification was conducted by evaluating linearity, precision, accuracy, limit of detection (LoD), and limit of quantification (LoQ). All parameters met the acceptance criteria based on ICH Q2(R1) and ISO/IEC 17025:2017 guidelines, with a determination coefficient (r²) of 0.9993, precision (%RSD) of 1.67%, and accuracy (% recovery) of 101.40%. The LoD and LoQ values were 7.06 ppm and 21.40 ppm, respectively, indicating the method's sensitivity in detecting and quantifying low concentrations of total phenolics. Although the analysis was conducted on green tea extract (Camellia sinensis), the method is generally applicable to various other plant extracts. These results demonstrate that the method is suitable for routine laboratory use and reliable for implementation in support of ISO/IEC 17025-based quality systems.